Impact of a novel interprofessional dental and pharmacy student tobacco cessation education programme on dental patient outcomes. Issue 1 (2nd January 2018) - Myers Virtue, Shannon; Rotz, Melissa E; Boyd, Matthew; Lykon, Jillian L; Waldron, Elizabeth M; Theodorou, Jacqueline
ABSTRACT: The dental setting presents a unique opportunity to assist patients with tobacco cessation. Many dental providers do not feel prepared to provide tobacco cessation, particularly with regard to education on pharmacological treatments. An interprofessional practice experience with dental and pharmacy students provides a novel approach to tobacco cessation in the dental setting, but it is not known whether such methods affect patient outcomes. The goal of the study was to examine the impact of a novel dental and pharmacy student tobacco cessation education programme on patient knowledge gained, barriers to utilising cessation medications, quit intentions, and quit behaviours as compared to standard care. Dental patients who were seen at the dental admissions clinic of a dental school on interprofessional care (IPC) days and received tobacco cessation education from the dental-pharmacy student team ( N = 25) were compared with dental patients at the clinic seen on Standard Care (SC) days ( N = 25). Patients completed a post-appointment survey and a 4-week follow-up survey. IPC patients reported greater perceived knowledge post-appointment and at follow-up regarding tobacco cessation compared with SC patients and had greater intentions to utilise medication to assist with tobacco cessation. At follow-up there were no differences between groups in terms of quit attempts. Among patients who made a quit attempt those in the IPC group were more likely to have set a quit date and contacted a provider for assistance regarding tobacco cessation. Dental-pharmacy student interprofessional tobacco cessation may be an innovative way to provide tobacco cessation education to dental patients and provide students with interprofessional practice experiences.